Dynamic damage identification for a full-scale parabolic tuff barrel vault under differential settlements of the supports. (12th July 2021) - Castellano, Anna; Camassa, Domenico; Fraddosio, Aguinaldo; Scacco, Jacopo; Piccioni, Mario Daniele; Milani, Gabriele
Highlights: A new damage dynamic identification approach for masonry arched structures. Both the location and the intensity of the damage can be reconstructed. Application to a masonry vault damage by vertical differential settlements of the supports. Validation of the proposed approach based on experimental data. Abstract: The vibration response of a full-scale polycentric near parabolic tuff barrel vault under differential settlements of the abutments are experimentally analyzed. During the experimental tests, the static and dynamic responses of the vault have been continuously monitored through a large number of sensors of different kinds placed in suitable points of the structure and supports. The data acquired by the accelerometric sensors are used for detection, localization, and quantitative assessment of the damage by means of a dynamic damage identification (DDI) procedure specifically developed for arches. Numerical models calibrated from experimental results are employed to evaluate the effectiveness of the proposed DDI approach. The position of the crack hinges related to the experimental and theoretical collapse mechanism of the vault, along with their actual depth, turn out to be effectively identified through the proposed DDI procedure, showing the capabilities of such an approach for assessing damage even in existing full-scale masonry constructions.